Precision Analysis of Noncircular Gears Based on CNC Machining Technology under Cloud Computing Platform - JianQing Dai; Wei Xu; FenFen OuYang (Shock and Vibration)
In order to solve the problem of machining error of noncircular gears, a method based on the analysis and research of the accuracy of noncircular gears based on CNC machining technology under the cloud computing platform is proposed to further improve the technical accuracy of noncircular gears. The error and error items are analyzed mainly, and a model framework based on cloud computing platform is proposed on this basis. The architecture of the system is deeply analyzed, focusing on the dynamic integration method of gear cloud measurement system resources based on cloud platform, building a gear cloud measurement system based on cloud computing platform, and testing needs to use Hadoop to install the software that needs to be prepared: virtual machine version, VMware Workstation-14.0.0 build-6661328, Linux version. The results show that the technical support of the cloud computing platform can effectively improve the accuracy of noncircular gears.